2020
DOI: 10.1101/2020.07.10.20150482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Repolarization Pattern and Suicidal Risks: A Single Center Case-Control Study

Abstract: Background: Early repolarization pattern was reported to be associated with mental illness. However, its role in patients with the suicidal risks remains unclear. Objective: The aim of this study is to examine the frequency of Early repolarization pattern in patients with the suicidal risks compared with the age matched medical checkups. Method: A retrospective analysis of 27 patients with a history of suicide risks, including suicide attempt and nonsuicidal self-injury, and a family history of suicide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The copyright holder for this preprint this version posted July 17, 2020. ; https://doi.org/10.1101/2020.07.16.20155838 doi: medRxiv preprint 5 sudden cardiac death [11,12]. Recently, it has been reported that there are associations between ERP and attention-deficit hyperactivity disorder [13,14],and the patients with suicidal risks [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted July 17, 2020. ; https://doi.org/10.1101/2020.07.16.20155838 doi: medRxiv preprint 5 sudden cardiac death [11,12]. Recently, it has been reported that there are associations between ERP and attention-deficit hyperactivity disorder [13,14],and the patients with suicidal risks [15].…”
Section: Introductionmentioning
confidence: 99%
“…ERP and J-point elevation pattern, which are not uncommon and often observed in younger and healthier people [10], are arrestive electrocardiographic patterns associated with sudden cardiac death [11,12]. Recently, it has been reported that there are associations between ERP and attention-deficit hyperactivity disorder [13,14],and the patients with suicidal risks [15]. Moreover, Fitzgerald et.al reported that Patients with serious mental illness, especially schizophrenia/schizoaffective disorder, exhibit a significantly high rate of abnormal late potentials on Signal-averaged electrocardiogram (SAECG) and ERP [16].…”
Section: Introductionmentioning
confidence: 99%